Local Fiscal Capacity Supports Poverty Reduction: Kapasitas Fiskal Daerah Mendukung Pengentasan Kemiskinan - Meisya Ayu Devina; M. Taufiq (Academia Open, 2026)
General Background: Poverty remains a central regional development challenge requiring employment creation, inclusive economic expansion, and adequate fiscal capacity. Specific Background: Bangkalan Regency recorded persistently higher poverty levels than East Java despite changing labor-market conditions, fluctuating economic performance, and rising locally generated revenue. Knowledge Gap: Previous studies reported inconsistent relationships between unemployment, economic growth, fiscal resources, and poverty, requiring location-specific time-series evidence. Aims: This study examines the effects of the open unemployment rate, economic growth, and locally generated revenue on poverty during 2000–2024. Results: A quantitative design used 25 years of secondary data from Statistics Indonesia and the Ministry of Finance, analyzed through multiple linear regression in EViews 12. The model satisfied normality, multicollinearity, heteroskedasticity, and autocorrelation diagnostics. Collectively, the three predictors were significant, F = 9.566761, p = 0.000350, with an adjusted R² of 0.517105. The open unemployment rate was not significant (β = −0.051679, p = 0.8703), and economic growth was also not significant (β = 0.117414, p = 0.7191). Locally generated revenue showed a significant negative coefficient (β = −0.038981, p = 0.0002). Novelty: The study simultaneously evaluates labor-market, macroeconomic, and fiscal determinants using a 25-year district-level series. Implications: Regional authorities should strengthen fiscal capacity, improve revenue allocation, and direct spending toward infrastructure, education, health, small enterprises, and inclusive economic opportunities. Highlights: Fiscal receipts showed β = −0.038981 with p = 0.0002. Labor-market participation yielded p = 0.8703; output expansion yielded p = 0.7191. The joint model reached p = 0.000350, explaining 51.71% of variance. Keywords: Economic Growth, Local Own Source Revenue, Open Unemployment Rate, Poverty